Multicore simulation of power system transients - Uriarte, Fabian M. (The Institution of Engineering and Technology, 2013)
This book shows how to partition and parallelize the simulation of power system transients on a multicore desktop PC.
Keywords: Electric lines.; Electric networks.; Transients (Electricity); Electric power systems.; elektronické knihy; electronic books